2022
DOI: 10.1021/acs.analchem.2c03579
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Resolved Electrochemiluminescence to Multiplex the Immunoassay and DNA Probe Assay

Abstract: The investigation on electrochemiluminescence (ECL) multiplexing bioassays mainly focuses on simultaneously detecting either proteins or nucleic acids. To overcome the limitation of a short waveband for spectrum-resolved ECL multiplexing bioassays, herein, a highly monochromatic (FWHM <40 nm) and bandgap-engineered ECL luminophore, that is, mercaptopropionic acid-capped and Zn2+-mediated aggregation-induced emission (AIE) assembly of Au nanocrystals (NCs) (Zn2+-AIE-AuNCs), of strong emission and the maximum em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, improving the efficiency and stability of Au NCs is of central importance in both fundamental research and practical applications. 30,31 The formation of rigid supramolecular structures via host-guest recognition by ligands is an effective method for improving the ECL performance of Au NCs. [32][33][34] Herein, a rigid supramolecular structure of Au NCs was prepared based on host-guest recognition between the ligands of 4-hydroxy-2-mercapto-6-methylpyrimidine (MTU) and L-arginine (Arg) with the aim of ECL enhancement of Au NCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, improving the efficiency and stability of Au NCs is of central importance in both fundamental research and practical applications. 30,31 The formation of rigid supramolecular structures via host-guest recognition by ligands is an effective method for improving the ECL performance of Au NCs. [32][33][34] Herein, a rigid supramolecular structure of Au NCs was prepared based on host-guest recognition between the ligands of 4-hydroxy-2-mercapto-6-methylpyrimidine (MTU) and L-arginine (Arg) with the aim of ECL enhancement of Au NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving the efficiency and stability of Au NCs is of central importance in both fundamental research and practical applications. 30,31 The formation of rigid supramolecular structures via host–guest recognition by ligands is an effective method for improving the ECL performance of Au NCs. 32–34…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO), δ (ppm): 8.74 (t, J = 7.5 Hz, 1H), 8.12 (dddd, J = 17.2, 13.0, 12.2, 5.9 Hz, 3 H), 7.93−7.86 (m, 1 H), 7.80 (t, J = 5.9 Hz, 1 H), 7.73−7.59 (m, 1 H), 7.59−7.50 (m, 1 H), 7.49−7.21 (m, 3 H), 7.05−6.94 (m, 1 H), 6.87 (t, J = 6.6 Hz, 1 H), 6.75−6.60 (m, 2 H), 6.52 (t, J = 6.7 Hz, 1 H), 6.27−6.11 (m, 1 H), 3.15 (dd, J = 11.5, 4.7 Hz, 2 H). 13 Synthesis of ECL-Probe. The ECL-probe was synthesized following the established protocol described in the literature.…”
mentioning
confidence: 99%
“…In recent years, electrochemiluminescence (ECL) technology has received considerable attention owing to its free external light sources, low background, rapid analysis, and miniaturization . As a powerful bioanalytical technique, ECL has demonstrated exceptional analytical performance for the detection of biomarkers at trace levels. , Apart from the traditional applications, such as amino acids, proteins, cells, metal ions, and other small molecules, their valuation in resistance genes remains largely unexplored so far. Very recently, Liu et al reported an ECL biosensing platform to sensitively detect methicillin-resistant Staphylococcus aureus (MRSA) resistance genes based on CdS quantum dots .…”
mentioning
confidence: 99%
“…Electrochemiluminescence (ECL), a powerful optical technology of low background noise, wide dynamic range, and high sensitivity, is being widely used for immunoassays , and DNA probe analyses. , An ECL assay is conducted in either a total-photon-collected or a wavelength-resolved way. The wavelength-resolved ECL is normally conducted with area array detectors, , such as charge-coupled devices , and complementary metal-oxide semiconductors. , Although the dispersion of ECL can enable multiple immunoassays without spectral cross-talk, , the ECL photons at a given wavelength are much less than the total ECL photons. From this point, the commercialized ECL immunoassay is normally conducted in a total-photon-collected way with a photomultiplier tube as a detector. , …”
mentioning
confidence: 99%